2010
DOI: 10.1152/ajpregu.00612.2009
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced reductions in transporter mRNA levels parallel reductions in intestinal sugar transport

Abstract: More than a century ago, ionizing radiation was observed to damage the radiosensitive small intestine. Although a large number of studies has since shown that radiation reduces rates of intestinal digestion and absorption of nutrients, no study has determined whether radiation affects mRNA expression and dietary regulation of nutrient transporters. Since radiation generates free radicals and disrupts DNA replication, we tested the hypotheses that at doses known to reduce sugar absorption, radiation decreases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 48 publications
3
22
1
Order By: Relevance
“…Our preliminary measurements of intestinal transport of sugars after a 3-day chronic irradiation with 6.8 Gy (0.094 Gy/h) showed that, unlike our findings for a 7 Gy acute irradiation (5), this absorbed dose did not affect their transport (data not shown). However, increasing the absorbed dose rate to 0.13 and 0.20 Gy/h, and the corresponding absorbed dose to 9.6 and 14.4 Gy, was sufficient to reduce transport of some sugars.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Our preliminary measurements of intestinal transport of sugars after a 3-day chronic irradiation with 6.8 Gy (0.094 Gy/h) showed that, unlike our findings for a 7 Gy acute irradiation (5), this absorbed dose did not affect their transport (data not shown). However, increasing the absorbed dose rate to 0.13 and 0.20 Gy/h, and the corresponding absorbed dose to 9.6 and 14.4 Gy, was sufficient to reduce transport of some sugars.…”
Section: Discussioncontrasting
confidence: 76%
“…These studies extend and expand on our earlier studies that investigated reductions in intestinal nutrient transport after acute whole-body exposure to 137 Cs gamma rays and the capacity of a vitamin ACE-enriched diet to protect against these reductions (4, 5). Accordingly, the focus of the current discussion is to compare our findings for chronic versus acute whole-body irradiation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In addition, the effects of chronic exposure to HZE particles on nutrient absorption, including radioprotectors must be considered. Earlier studies indicated that nutrient absorption in mice was significantly reduced following the exposure to c rays (217,239). Decreases in intestinal sugar absorption were associated with a rapid decrease in SOD and catalase abundance, followed by dramatic upregulation within 4 h and then downregulation a few days later (238).…”
mentioning
confidence: 95%